Generalization of the Theoretical Science Conditions on the Sustainable Development of the Enterprise - Касич, А.; Яковенко, Я. (Київський національний університет імені Тараса Шевченка, 2019)
The article is devoted to the main provisions of theoretical science concerning sustainable development and its formation according to the chronological order of its components. The article is considered all the main civilization approaches to the sustainable development and provides an analysis of the views of contemporary Ukrainian and foreign scientists on the ways of its implementation. Particular importance is paid to the study of the concept of sustainable development in the context of economic schools and concepts.

Присвячено дослідженню основних положень теоретичної науки щодо стійкого розвитку та формуванню в хронологічному порядку його складових. Розглянуто основні цивілізаційні підходи до стійкого розвитку та подано аналіз поглядів сучасних українських і зарубіжних учених щодо шляхів його запровадження. Особливе значення надається дослідженню концепції стійкого розвитку в розрізі економічних шкіл і понять.
Узагальнення положень економічної науки щодо стійкого розвитку підприємства
Keywords: стійкий розвиток підприємства; підходи до запровадження стійкого розвитку; sustainable development; sustainability; approaches to the introduction of sustainable development